2022
DOI: 10.1007/s10143-021-01722-y
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative myocardial injury after elective neurosurgery: incidence, risk factors, and effects on mortality

Abstract: BackgroundPerioperative myocardial injury is an important reason of mortality and morbidity after neurosurgery. It usually is missed due to asymptomatic character. In the present study, we investigated myocardial injury after noncardiac surgery (MINS) incidence, the risk factor for MINS and association of MINS with 30-day mortality in neurosurgery patients. MethodsPatients with cardiac risk who underwent elective neurosurgery were enrolled to the study. The patients' demographics, comorbidities, medications us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The risk of perioperative cardiac events is more significant for patients undergoing neurosurgical procedures who have chronic antiplatelet and antithrombotic therapy interrupted perioperatively [ 2 ]. Utilizing postoperative high-sensitivity troponin levels, a prospective cohort study identified perioperative myocardial injury in 20.5% of patients undergoing elective neurosurgery [ 3 ]. Patients undergoing oncologic surgery may face even greater perioperative risks, with one population-based study identifying a more than twofold increase in the incidence of arterial thromboembolism and myocardial infarction in the first 6 months following a new diagnosis of cancer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of perioperative cardiac events is more significant for patients undergoing neurosurgical procedures who have chronic antiplatelet and antithrombotic therapy interrupted perioperatively [ 2 ]. Utilizing postoperative high-sensitivity troponin levels, a prospective cohort study identified perioperative myocardial injury in 20.5% of patients undergoing elective neurosurgery [ 3 ]. Patients undergoing oncologic surgery may face even greater perioperative risks, with one population-based study identifying a more than twofold increase in the incidence of arterial thromboembolism and myocardial infarction in the first 6 months following a new diagnosis of cancer [ 4 ].…”
Section: Introductionmentioning
confidence: 99%